Representations of human nature within recurrence in history: A comparative study of Lord of the Flies and the Things They Carried - Arikan, Seda (Common Ground Publishing, 2016)
The phenomenon of historic recurrence is frequently emphasized by many philosophers, writers, and scientists. Many intellectuals try to find an answer to the question of why similar events occur in different periods of history. Although various answers are given, their common point lies in the nature of human being, who creates the historic recurrence. In this respect, literature appears as a significant tool because it depicts similar experiences in infinitive history. This study examines two novels, William Golding's Lord of the Flies and Tim O'Brien's The Things They Carried in terms of recurrence of history and its relation to the nature of human being. The common point those novels share is the psychological and unconscious tendency of human to create a primitive circumstance when s/he is isolated from civilization. In this respect, this study handles the primitive and/or civilized nature of human when left in life-anddeath struggles. It also presents the paradoxical "liberium arbitrium" in terms of conscience, ethics, and human nature. © Common Ground, Seda Arikan, All Rights Reserved.
Keywords: Evil by nature; Historic recurrence; Primitiveness and civilization